Influence of ventilation and media on potato (Solanum tuberosum L.) tuberization and its growth characteristics - Mobini, Saeid Hassanzadeh; Ismail, Mohd Razi; Arouiee, Hossein (Academic Journals, 2009)
Considering the most suitable relationship between ventilation and media in this study, two mixtures of perlite and coir (3:1, light and 1:3, heavy v/v) were applied to determine the growth characteristics var. Sante of potato plantlets. As potato has high potential in minituber production, different levels of supplemental aeration (0, 12.5, 25 and 75%, v/v/min) were compared for providing root oxygen demand and increasing potato minituber yield. Applying sufficient aeration led to significant increase in dry matter, number, size, quality of minituber and most of the growth parameters such as leaf area index (LAI), leaf area index duration (LAID), harvest index (HI) and root : shoot ratio. The results showed that by applying aeration at 25% (v/v/min), tuber yield was increased significantly up to 162% and increase in tuber number was predominant at the rate of 3678 tuber/m2. Desirable performance of aerated plant can be resulted from root oxygen demand of potato which is higher than normal ventilation in media. Heavy media was more responsive to aeration than light one. Thus, aeration at 25 and 12.5% (v/v/min) in heavy and light media respectively was considered as favorable level in rizo-sphere and had positive effect on tuberization.